Crossing Phantom Divide in f(Q)f(Q) Gravity. Issue 8 (23rd June 2022) - Arora, Simran; Sahoo, Pradyumn Kumar
Abstract: The possibility of crossing a phantom divide line in the extension of symmetric teleparallel gravity or the f ( Q ) f(Q) gravity, where Q is the non‐metricity, is investigated. The cosmic evolution of the effective equation of state parameter for dark energy is studied considering exponential, logarithmic, and combined f ( Q ) f(Q) theories. Moreover, the exponential model behaves like the ΛCDM at high redshifts before deviating to ω eff < − 1 ω _eff<-1 or ω eff > − 1 ω _eff>-1, respectively, depending on the value of model parameter. It also approaches a desitter phase asymptotically. However, the crossing of the phantom divide line, that is, ω = − 1 ω = -1, is realized in the combined f ( Q ) f(Q) theory. Furthermore, statefinder diagnostics are studied in order to differentiate between several dark energy models. To ensure the three model's stability, the stability analysis is employed using linear perturbations. It is demonstrated how to reassemble f ( Q ) f(Q) via a numerical inversion approach based on existing observational constraints on cosmographic parameters and the potential of bridging the phantom divide in the resulting model. It explicitly demonstrates that future crossings of the phantom dividing line are a generic feature of feasible f ( Q ) f(Q) gravity models. Abstract : In this article, the authors investigate the possibility of crossing a phantom divide line in the f ( Q ) f(Q) gravity, where Q is the nonmetricity. They study the cosmic evolution of the effective equation of state parameter for dark energy (DE) considering exponential, logarithmic, and combined f ( Q ) f(Q) theories. The authors observe the crossing of the phantom divide line in the combined f ( Q ) f(Q) theory. Furthermore, they study the statefinder diagnostics to differentiate DE models and observe that the model is stable using linear perturbations.